The reverse of Socrates: Xanthippe and the place of women in the history of Philosophy - Silva, Rafael Guimarães Tavares da; Anjos, Sara Camila Barbosa dos (Argumentos - Revista de Filosofia, 2024)
In the history of Philosophy, Socrates is represented as an individual with a firm and temperate character, although intellectually restless, whose investigations inaugurate reflections of a properly ethical nature within the scope of ancient thought. Its historical position is considered so central that he is chosen as the term for the periodization of Ancient Philosophy (with its philosophers currently organized around the curious notion of “pre-Socratics”). His wife, Xanthippe, on the other hand, is represented by ancient biographical tradition as ill-tempered, willful, and intemperate. In several anecdotes, she embodies the opposite of everything expected of a philosopher. In order to reflect on some constructions based on gender aspects within the history of Philosophy, we will analyze the metonymic value that representations of Socrates, Xanthippe and other female figures from his surroundings acquire in philosophical works, especially those composed by Plato.